Retroutopia. On the idea of work and progress in (post)socialist society - Potkonjak, Sanja (Array, 2014)
The modernist project of Yugoslav socialism was guided by the concepts of progress, prosperity and the New Man. Those concepts had been lingering on utopian ideas and produced a discourse that acknowledged and made possible „the illusion of a better future“. With the fall of socialism, the post-Yugoslav, transitional societies witnessed the decline of specific social values such as solidarity and „welfare state“ that have been providing the basis for the „future-based illusions“. Drawing on general disillusion with economic changes after the 1990s, citizens and the whole communities started to express fear and insecurity of their immediate future. This paper draws upon post-socialist anthropology, anthropology of work and economic anthropology to show how global-scapes of economy affected local industrial settings that were undergoing economic change. Our research emerged in the context of industrial labor and steel-industry in Croatia. This article focuses on historical and ethnographic analysis on discourse of socialist labor newspapers and outcomes of ethnographic research on industrialization and deindustrialization in the town of Sisak. The aim of the paper is to analyze contemporary narratives on work that are continuous, overlapping and sometimes diverging from the socialist vocabulary of labor journalism. The paper is using everyday narratives of ex-steel-industry workers to illustrate and broaden the understanding the workers have of socialism and transition. On one hand it explores the narratives of work by examining how they relate to the role of post-socialist state in overcoming the crisis and the decline of steel industry. On the other hand it looks at how new narratives are evoking the (retro)utopian discourse on the future of work.